ECSCW 2003 Proceedings of the Eighth European Conference on Computer Supported Cooperative Work 14–18 September 2003, Helsinki, Finland - Kuutti, Kari; Karsten, Helena; Fitzpatrick, G.; Dourish, Paul (Springer Netherlands, 2003)
th This volume gathers together the technical papers presented at the 8 European Conference on Computer Supported Cooperative Work (ECSCW), held in Helsinki Finland. ECSCW is an international forum for multidisciplinary research covering the technical, empirical, and theoretical aspects of collaboration and computer systems. The 20 papers presented here have been selected via a rigorous reviewing process from 110 submissions. Both the number of submissions and the quality of the selected papers are testimony to the diversity and energy of the CSCW community. We trust that you will find the papers interesting and that they will serve to stimulate further quality work within the community. The technical papers are complemented by a wider set of activities at ECSCW 2003, including tutorials, workshops, demonstrations, videos, posters and a doctoral colloquium. Together these provide rich opportunities for discussion, learning and exploration of the more recent and novel issues in the field. This conference could not have taken place without considerable enthusiasm, support and participation, not to mention the hard work of a number of people. In particular, we would like to thank the following: • The authors, representing over 17 countries and 97 institutions, who submitted a paper. So many submissions of such high quality are the basis of a good conference. • The members of the program committee who so diligently reviewed and discussed papers. Their collective decisions result in a good scientific program and their feedback to authors strengthens the work of the community